UNIVERSITY GREEN SPACES SUSTAIN BIRDS, BUT HABITAT DIVERSITY IS KEY - Iram Rafique; Rehan Ul Haq; Arshad Javid (Journal of Animal and Plant Sciences, 2025)
University campuses with expansive green spaces and limited human presence for much of the day can offer excellent habitats for birds. However, environmental and anthropogenic factors can significantly impact bird populations. The present study aimed to investigate the effects of climatic, hydrological, and landscape variables, as well as anthropogenic disturbance, on the population dynamics of birds from June 2022 to June 2023 at the University of Veterinary and Animal Sciences, Ravi Campus, Pattoki, Pakistan. The point count method was utilized to record bird observations, generalized linear mixed models were applied to assess the effects of these variables on bird abundance and species richness, while generalized additive mixed models were applied to identify the threshold for each effect. Through the 12 months of the study, 64,657 individuals of 117 bird species belonging to 47 families were observed at the university campus. Bird abundance declines as distance from human settlements increases, suggesting that human-modified landscapes may support avian populations. Species richness decreases with rising minimum temperatures. Among the hydrological variables, increasing water depth negatively affected overall species richness, with a decline observed after 1.2 m. In conclusion, university campuses have the potential to serve as significant avian hotspots, and their ecological value can be further enhanced by providing a combination of natural areas and human-modified habitats, which may help mitigate the effects of environmental variables.
Keywords: Climate impact; Green campuses; Green spaces; Landscape planning; Mixed modelling; Population dynamics